Perancangan Sistem Informasi Manajemen Dalam Pengelolaan Data Kepegawain Di Kantor Dinas Perkebunan Provinsi Sumatera Utara - Darkani, M. Farhan; Muliono, Rizki (INCODING: Journal of Informatics and Computer Science Engineering, 2024)
The use of this information system will provide convenience for the North Sumatra Plantation Service in managing employees, especially in terms of inputting employee data. In connection with the data input mechanism still using the classic method, namely using MS Excel, which the author considers to be less flexible. Therefore, through this Internship, the author hopes to be able to design a web application where employees can input their data more easily and flexibly. The creation of this system starts from data collection, system analysis, system design and implementation.